Evaluation of some physical, chemical, and biological characteristics of the traditional Al-Jabal Al-Akhdar carob Rub "Libya" - Abdalrasol Awad Bo Sultan; Mabruka milad mwsaa; Hanan Mahmoud Saleh (مجلة البيان العلمية, 2023)
The aim of this research was to study of some physical, chemical, biological and functional properties of carob Rub produced by traditional methods in Al Jabal Al Akhdar region, where seven samples of carob rub were purchased from the local market in a random manner. The results were the total solids, dissolved solids, moisture, pH and color are (59.76±6.46%, 57.94±6.73%, 40.23±6.46%, 5.23±0.26, L*21.14±0.18 a*-26.00±0.16 b* 0.53±0.02) respectively. While the average percentage of acidity, total sugars, reducing sugars, sucrose, ash, protein and hydroxymethylfurfural compound were 0.57 ± 0.16%, 41.99 ± 7.50%, 15.42 ± 1.11%, 26.57 ± 6.39%, 1.47 ± 0.50%, 23.15 ± 0.07 mg/kg) respectively. Regarding the biological properties, the mean of total phenols, flavonoids, tannins, and antioxidant activity were DPPH, ABTS (6.082 ± 0.06mEqGA/100g , 2.339 ± 0.05mEq/100 g Catechins, 3.125 ± 0.91% , 35.69 ± 0.14 , 519.38 ± 4.18) respectively, and the studied functional property, which is the ability to emulsify, was ( 10.3% ±0.15).